2010
DOI: 10.1146/annurev.soc.012809.102635
|View full text |Cite
|
Sign up to set email alerts
|

Historical Studies of Social Mobility and Stratification

Abstract: This review discusses historical studies of social mobility and stratification. The focus is on changes in social inequality and mobility in past societies and their determinants. It discusses major historical sources, approaches, and results in the fields of social stratification (ranks and classes in the past), marriage patterns by social class or social endogamy, intergenerational social mobility, and historical studies of the career. 429Annu. Rev. Sociol. 2010.36:429-451. Downloaded from www.annualreviews.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(40 citation statements)
references
References 98 publications
0
37
0
Order By: Relevance
“…However, pure bilateral relationships (Heide, 1994) are rare (Hingley, 2005a;Kumar, 2005). Usually, one firm has more to gain from a relationship (Blossfeld, 2009;van Leeuwen & Mass, 2010) and opportunism varies greatly among leading firms (Heide, 1994). SET's view of inter-firm relationships as involving complex and dynamic interactions and tradeoffs becomes a preferable theoretical foundation for examining such relationships.…”
Section: Relationship Benefitsmentioning
confidence: 99%
“…However, pure bilateral relationships (Heide, 1994) are rare (Hingley, 2005a;Kumar, 2005). Usually, one firm has more to gain from a relationship (Blossfeld, 2009;van Leeuwen & Mass, 2010) and opportunism varies greatly among leading firms (Heide, 1994). SET's view of inter-firm relationships as involving complex and dynamic interactions and tradeoffs becomes a preferable theoretical foundation for examining such relationships.…”
Section: Relationship Benefitsmentioning
confidence: 99%
“…The empirical work on status attainment dates back to the Blau & Duncan, who concluded that both ascribed status (parental education and occupational status) and achieved status (education and prior occupational status) are important factors accounting for an individual's ultimate attained status (Blau & Duncan, 1967). By recasting status as class (Goldthorpe et al, 1980) and adding socio-economic factors (Sewell, Hauser, Alwin, Ellegaard, & Fisher, 1975), scholars have further advanced the Blau & Duncan Model, making it a good basis for analyzing the making of the middle class at the micro-level in both developed and developing economies (Bian, 2002;Van Leeuwen & Maas, 2010). It is of note that China's Hukou System may impact status attainment for those without urban hukou registrations fundamentally (Chan, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A key interest has revolved around the extent to which social mobility regimes differ between countries at different levels of development or with a different institutional structures, and whether these patterns changed during and after industrialization (see, e.g., Bourdieu, Ferrie and Kesztenbaum 2009;Breen 2008;Erikson and Goldthorpe 1992;Ferrie 2005;Ganzeboom, Luijkx and Treiman 1989;Ganzeboom, Treiman and Ultee 1991;Grusky and Hauser 1984;Hout and DiPrete 2006;Lipset and Bendix 1959;Ferrie 2007, 2013;Treiman 1970;Van Leeuwen and Maas 2010). In turn, these questions are also related to issues of social stratification more generally, and the extent to which these patterns are dependent on economic development (see, e.g., Treiman 1976).…”
Section: Introductionmentioning
confidence: 99%